A concise guide to good practices for automated testing and documentation of Research Software - Fritz, Jakob; Mesiti, Michele; Thiele, Jan Philipp (Electronic Communications of the EASST, 2025)
This publication aims to highlight aspects of good practices from the areas of testing, documentation, and workflow management to improve existing code in Research. Applying these practices helps to make the scientific results obtained with the software easier to reproduce, as the codebase is easier to understand (thanks to documentation) and it is ensured that the code works as expected (thanks to automated testing). As codebases grow larger, workflow management for automated testing is also needed in order to keep the development cycle fast.